Higher rates of non-skeletal complications and greater healthcare needs in achondroplasia compared to the general UK population: a matched cohort study using the CPRD database - Jeanne M. Pimenta; Melita Irving; Moira Cheung; Louise Mazzeo; Sarah Landis; Swati Mukherjee (Orphanet Journal of Rare Diseases, 2023)
Abstract Background The natural history of skeletal complications in achondroplasia (ACH) is well-described. However, it remains unclear how the rates of non-skeletal complications, surgical procedures, healthcare needs and mortality differ between individuals with ACH and the general population. This study aimed to contextualise the extent of these outcomes by comparing event rates across the lifespan, between those with ACH and matched controls in a United Kingdom (UK) population. Methods This retrospective, matched cohort study used data from national UK databases: the Clinical Practice Research Database (CPRD) GOLD from primary care, the secondary care Hospital Episode Statistics (HES) databases and the Office of National Statistics mortality records. ACH cases were identified using disorder-specific Read Codes or International Classification of Diseases 10th Revision codes. For each ACH case, up to four age- and sex-matched controls (defined as those without evidence of skeletal/growth disorders) were included. Event rates per 100 person-years were calculated for a pre-defined set of complications (informed by reviews of existing ACH literature and discussion with clinical authors), healthcare visits and mortality. Rate ratios (RRs) with 95% confidence intervals (CIs) were used to compare case and control cohorts. Results 541 ACH cases and 2052 controls were identified for the CPRD cohort; of these, 275 cases and 1064 matched controls had linkage to HES data. Approximately twice as many non-skeletal complications were reported among individuals with ACH versus controls (RR [95% CI] 1.80 [1.59–2.03]). Among ACH cases, a U-shaped distribution of complications was observed across age groups, whereby the highest complication rates occurred at < 11 and > 60 years of age. Individuals with ACH had greater needs for medication, GP referrals to specialist care, medical imaging, surgical procedures and healthcare visits versus controls, as well as a mortality rate of almost twice as high. Conclusions Patients with ACH experience high rates of a range of both skeletal and non-skeletal complications across their lifespan. To manage these complications, individuals with ACH have significantly increased healthcare needs compared to the general population. These results underscore the need for more coordinated and multidisciplinary management of people with ACH to improve health outcomes across the lifespan.